Optimization of effective parameters in the biosorption of Cr(VI) using acid treated date palm fiber from aqueous solution. Issue 11 (2nd March 2016) - Hossini, H.; Esmaeili Taheri, H.; Arab Markadeh, A.; Rezaee, A.; Rastegar, S.O.
Abstract: The study tries to determine the optimal condition to achieve the maximum Cr(VI) removal in the biosorption process from aqueous solution using acid-treated date palm fiber as the biosorbent. Three factors including initial pH, initial Cr(VI) concentration, and biosorbent dosage were optimized using response surface methodology. Maximum Cr(VI) removal was 95% at the optimum condition of initial pH 3.3, initial Cr(VI) concentration 180 (mg/L), and biosorbent dosage of 0.8% (w/v). The kinetic study was done to acquire a deeper understanding of the mechanism of biosorption process and its results showed that the pseudo-second-order models controlled the process. Isotherm study showed that Langmuir model described the experimental data thoroughly.